Faktor-Faktor yang Memengaruhi Pemanfaatan Cyber Extension oleh Penyuluh Pertanian Lapangan (PPL) di Kabupaten Bima - Nurul Fadillah; Dwiningtyas Padmaningrum; Eksa Rusdiyana (Universitas Sebelas Maret, 2024)
Cyber extension is a website-based application that provides information related to agriculture. Field agricultural extension workers (PPL) in Bima Regency still have not optimized the cyber extension function to share information. This research aims to analyze the influence of PPL and cyber extension innovation characteristics on the use of cyber extension by PPL in Bima Regency. This research uses a quantitative approach, and data analysis uses multiple linear regression tests. The research results show that age (X1) and formal education (X2) do not affect the use of cyber extension by PPL in Bima Regency. Non-formal education (training) (X3) and characteristics of cyber extension innovation (X4) have a positive effect on the use of cyber extension by PPL in Bima Regency. Thus, the intensity of cyber training can be increased to 4 times a year. Emphasizing the aspect of writing articles, the information shared can be developed so that it can vary in the form of video, audio in the form of podcasts, and also documentation in the form of photos of activities.